Persuasive language in multicultural social media marketing: A multimodal analysis of Tesla Asia’s advertisements on X/Twitter posts - Hasyim, Fuad (Universitas Islam Sultan Agung, 2025)
Social media marketing is a vital component of contemporary marketing strategies. Companies have realized that utilizing persuasive language through social media enables them to connect with and engage broader audiences. This research aims to investigate the persuasive language employed by Tesla Asia in multicultural social media marketing. The research was qualitative, employing content analysis of a dataset comprising Tesla Asia’s X (formerly Twitter) posts from April to June 2025. Tweets were categorized by persuasive technique based on Cialdini’s framework and analyzed for cultural targeting using Hofstede’s dimensions. Supplementary visual and compositional analysis was conducted to assess the interplay of image and text. The result presented that Tesla tailored its messaging and visual strategies to align with cultural values in each market, utilizing principles of Liking, Reciprocity, Social Proof, and Authority. By incorporating local references and appeals to the community, their content reflects values of respect and togetherness. An analysis of tweet engagement shows that culturally customized posts receive more likes and retweets, indicating stronger connections with specific audiences. This research provides insight into the cross-cultural adaptation of persuasive strategies on social media, underlining the importance of cultural sensitivity and localized strategies.